Discovery of a novel, liver-targeted thyroid hormone receptor-β agonist, CS271011, in the treatment of lipid metabolism disorders - Lin, Suwen; Huang, Shengjian; Deng, Zhou; Zhang, Yu; Huang, Lin; Wu, Yanyi; Lv, Shuyan; Wang, Zhiyi; Huang, Ning; Wang, Lan; Chen, Ziqi; Yu, Guangyin; et al. (Frontiers in Endocrinology, 2023)
Thyroid hormone receptor β plays a critical role in metabolism regulation and has become an attractive target for treating lipid metabolism disorders in recent years. Thus, we discovered CS271011, a novel THR-β agonist with higher activation of THR-β in vitro and similar effects with MGL-3196 in vivo, a phase III THR-β agonist for treating hyperlipidaemia and non-alcoholic steatohepatitis. CS271011 demonstrated favourable pharmacokinetic properties in mice and was enriched in the liver. Finally, we observed that CS271011 improved dyslipidaemia and reduced liver steatosis in the diet-induced obesity murine model. Mechanistically, CS271011 and MGL-3196 showed potent regulation of lipid metabolism-related genes. In conclusion, CS271011 is a potent and liver-targeted THR-β agonist for treating lipid metabolism disorders.